From Chatting to Cheating: How Can Ethical Considerations Be Ensured in this AI-Driven Research Era? - Mohamed, Benaissa; Attou, Youness; Seddik, Mahmoud; Abdelhamid, Nfissi (International Journal of Language and Literary Studies, 2025)
It is crystal clear that Artificial Intelligence has revolutionized research methodologies, particularly in the realm of data collection and analysis. Chatbots, powered by AI algorithms, are increasingly utilized as research tools, facilitating data collection, participant engagement, and even data analysis. However, the integration of AI-driven methodologies raises profound ethical concerns, particularly regarding privacy, informed consent, and the potential for manipulation. Thus, this paper aims at exploring the intersection of chatting, as a mode of interaction, and cheating, as an ethical concern, within the context of AI-driven research. Specifically, it investigates how AI-powered chatbots, often employed as research tools, can inadvertently facilitate unethical behavior, such as cheating in academic or experimental settings. Drawing upon ethical frameworks and guidelines established in the field of research ethics, this paper proposes strategies and guidelines for researchers to ensure the ethical conduct of AI-driven research. Furthermore, this paper examines the implications of AI-driven research on academic integrity and scientific rigor. It discusses the challenges of maintaining transparency and accountability in AI-driven research processes, particularly in ensuring the validity and reliability of data collected through chatbot interactions. Briefly, by critically evaluating the ethical implications of AI-driven research methodologies, this paper aims to contribute to the development of responsible and ethically sound practices in the field of research utilizing AI technologies.